The effects of listening exposure in english learners’ speaking skill among students from eighth grade, sections A and B, from Complejo Educativo Walter A. Soundy, Santa Tecla City, La Libertad, 2015 - Deras Rodríguez, Andrés Antonio
The English language is one of the most dominant languages throughout the world; for that reason, in many cases, it is necessary to speak English to have better life conditions such as a better job, education, goods, etc. One of the most common issues that people tend to have while learning English is that they are not capable of producing the language orally; some English learners are able to understand the spoken language, but when they are asked to have an English conversation they fail because they have not developed the speaking skill. Therefore, the present research project aims to determine the effects of listening exposure in English learners’ speaking skill among students from eighth, sections A and B, from Complejo Educativo WALTER A. SOUNDY, Santa Tecla City, La Libertad, 2015. The researchers focused on planning and teaching the English class by using listening activities such as videos, songs, dialogues, etc. to expose the students to the target language. This study focuses on how using listening activities in the classroom helps students develop the target language, specifically students´ speaking skill. The researchers focused the study based on Stephen Krashen’s theories about the Acquisition Learning Hypothesis, the Input and Output Hypothesis, the Direct method; and Tracy Terrel´s Natural Approach. Besides that, the researchers explain the importance of planning and implementing listening activities in the classroom to build students´ confidence at the time to speak English. Additionally, the researchers have taken into account that nowadays, technology can be useful to teach English, and English teachers can take advantage of it to develop a class; therefore, there are a lot of useful materials that can be found in internet that can help the teachers to develop the class, so the research team wants to increase English teachers´ awareness of how to use the equipment and materials to implement listening activities inside the classroom, and show how students can feel confident with this type of activities to learn a foreign language. This research was implemented to improve students´ speaking skill by being exposed to listening activities, so it can be said that this research will provide benefits to the school, the English teachers at the school, students, and the research team.